STUDI AWAL KARAKTERISTIK POLA RESISTIVITAS SISTEM PANAS BUMI TEMPERATUR RENDAH-MENENGAH DI INDONESIA - Dadan Wildan; Syafrima Wahyu (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Electrical resistivity is a common geophysical method to identify component in geothermal system. Resitivity value is affected by porosity, fluid saturation, temperature, salinity and the most important is type/proportion of clay minerals. By using geoelectric method resistivity values obtained at low – intermediate temperature of the geothermal system oka, wai selabung, banda baru, maranda, sembalun and bonjol, for clay cap and reservoir are between 8 – 50 Ωm and 50 – 250 Ωm respectively. The low resistivity is possibly due to occurrence of smectite and chlorite which formed on temperature < 180oC with Cation Exchange Capacity (CEC) value ranging from 120 -10. Keywords: Geothermal System, resistivity, clay minerals, CEC.